Overview of milling implements for grinding trees and shrubs - Gordeychik Andrey; Ariko Sergey; Mokhov Sergey; Sokolova Viktoriia; Saaya Sai-Suu; Zagidullin Ramil; Miroshikhina Ekaterina (E3S Web of Conferences, 2024)
The article describes the main consumers of milling tools (mulchers and rotovators) in the context of the sectors of the national economy, considers the classification features and features of the design and layout of these tools on energy carriers. The range of the main manufacturers of milling tools in the Russian Federation, the Republic of Belarus, countries of near and far abroad is described. It is noted that, despite the effectiveness of the use of tracked vehicles in a number of operating conditions, about 95% of this equipment has a wheeled propulsion type. Special attention is paid to the delimitation of the scope of mulchers and rotovators, as well as the possibility of using disk attachments for shredding trees and shrubs.